2012
DOI: 10.4048/jbc.2012.15.3.371
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous Mastitis during Chronic Antidepressant Therapy: Is It Possible a Conservative Therapeutic Approach?

Abstract: Granulomatous mastitis is a rare benign inflammatory disease of the breast with multiple etiologies such as tuberculosis, sarcoidosis, foreign body reaction, and mycotic and parasitic infections. In contrast, idiopathic granulomatous mastitis (IGM) is characterized by the presence of chronic granulomatous lobulitis in the absence of an obvious etiology. Clinically and radiologically it may mimic breast carcinoma and so awareness of surgeons, pathologists, and radiologists is essential to avoid unnecessary mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…High levels of prolactinemia in the cases of IGM on antidepressant therapy, suggests a possible side effect of selective inhibitors of serotonin reuptake (SSRI). Also, a functional crosstalk between serotonin and dopamine receptors is noteworthy [22][23][24]. Bellavia et al [22] reported that the cases of IGM related to the chronic use of antidepressant therapy should be treated with non-surgical therapeutic approaches, where possible, a conservative approach based on administration of an antiinflammatory therapy is favoured.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of prolactinemia in the cases of IGM on antidepressant therapy, suggests a possible side effect of selective inhibitors of serotonin reuptake (SSRI). Also, a functional crosstalk between serotonin and dopamine receptors is noteworthy [22][23][24]. Bellavia et al [22] reported that the cases of IGM related to the chronic use of antidepressant therapy should be treated with non-surgical therapeutic approaches, where possible, a conservative approach based on administration of an antiinflammatory therapy is favoured.…”
Section: Discussionmentioning
confidence: 99%
“…An immune-related pathophysiology due to oozing of secretions from milk ducts into lobules during pregnancy and lactation has been widely considered [1][2][3]. Reports of association of the disease with autoimmune disorders such as erythema nodosum, sarcoidosis, Wegener's granulomatosis, giant cell arteritis, or polyartheritis nodosa strengthens the theory [1,3,6]. The disease has also been seen after local trauma and consumption of anti-depressant drugs, perhaps due to hyperprolactinemia, as well as other granulomatous disorders as granulomatous thyroiditis, prostatitis and orchitis [2,6].…”
Section: Discussionmentioning
confidence: 91%
“…Methotrexate and azathioprine have proved helpful in some of these cases [1,4]. Steroids or methotrexate may eliminate the need for surgery [6]. A large review has demonstrated complete resolution of the lesions in 6 to 12 months with one or several of the above treatment plans [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations